An Analysis of the Online Teaching and Learning in Clothing and Textiles Programmes in Zimbabwe's Institutions of Higher Learning. - Tshuma, Senzeni; Chuma, Chipo; Mutungwe, Edlight (Eastern African Journal of Humanities & Social Sciences, 2025)
The coronavirus, because of its contagious nature, came with many adjustments to our daily lives. One of the adjustments is how teaching and learning is done across the board from primary schools to institutions of higher learning. The purpose of this study was to analyse the online teaching and learning in clothing and textiles programmes in Zimbabwe's institutions of higher learning. This is especially in the light of practical subjects such as Clothing and Textiles, which, are supposed to include practical and hands-on activities. The study selected three lecturers and thirty students from the three institutions of higher learning that delivered online lectures in Clothing and Textiles. In-depth interviews, questionnaires, and observation sheets were the instruments used to collect the data. The collected was analysed both qualitatively and quantitatively in line with convergent imperatives for triangulation and validation purposes. The TPACK was used as a theoretical lens to guide this inquiry. The findings revealed lack of suitable applications and software for virtual prototyping for the online teaching of the practical component of Clothing and Textile programs in higher education institutions in Zimbabwe. It was concluded that the lack of resources renders online teaching and learning as a pedagogical black box, as the lecturers become hand-capped to effectively teach for enhanced student comprehension. The study recommended that Clothing and Textiles departments in Zimbabwe encourage the design of online practical modules for use by lecturers in times of pandemics.